ANALISIS STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN PRODUK PADA MANDIRI STORE - Nuriawati; Mohammad Hosen; Muhammad Rofek; Jodi Eriyanto; M. Shohib (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2024)
Toko Mandiri Store, in carrying out a marketing strategy is to determine the target market by applying a number of elements, namely: segmentation, targeting and positioning and also with a marketing mix with the aim of persuading consumers and maintaining the number of existing customers. Toko Mandiri Store practices digital marketing strategies online through social media such as Facebook, diagrams and other internet networks that are connected to a wider range of consumers. Mandiri Store collaborates with Zalora, an online media sales market place that can be accessed globally. The aim of this research is to increase internet/online sales at the Mandiri Store, which has so far been less than optimal.